Russell: Government, Labour, and Business Progressivism in a Canadian War Industry, 1899-1920 - Pritchard, Kyle (University of Guelph, 2017)
In May 1919, businessman and former munitions manufacturer Thomas Russell was brought before the Royal Commission on Industrial Relations (Mathers Commission) to provide insight into the largest collection of strikes in Canadian history. Russell was one of Canada’s pioneering automakers, first employed as general manager of the Canada Cycle and Motor Co. (CCM) and later as vice-president when the company was reorganized to become the Russell Motor Car Co. (RMCC). Russell had been actively engaged in business and political discourse for nearly two decades and played a leading role in implementing industrial reforms during the First World War. The RMCC became the largest private producer of shell fuses in Canada and employed one of the country’s largest female workforces. While these progressive reforms increased the productivity and profitability of munitions manufacturers, they had been implemented with little regard to their dramatic transformation of wartime labour conditions. As the war came to a close, Russell suspended his seemingly “progressive” program in favour of protecting his companies’ enormous late war profits. When asked what he believed to be the cause of labour unrest, he told the Mathers Commission that the strikes were not the fault of employers’ wartime industrial policies, but rather an unavoidable “natural desire for betterment” among dissatisfied workers and the unemployed. Contrary to Russell’s testimony, employers were very much responsible. This project explores the origins of progressive ideals in Canadian business at the turn of the 20th century and their impact on industrial reform during the First World War. As war manufacturers, business progressives failed to address the devastation their industries caused in the post-war period. Their post-war factory closures and reluctance to compromise with the growing labour movement substantially contributed to the outbreak of the 1919 labour revolt and fueled future advocacy for government intervention in the Canadian economy.